BIMBINGAN DAN PELATIHAN SENI MERAJUT BAGI IBU-IBU ANGGOTA KOMITE SEKOLAH SDN LOWOKWARU 3 MALANG - Ellyn Eka Wahyu; Pudji Herijanto; Siti Nurbaya; Halid Hasan; Bambang Suryanto (Publisher UPT P2M Politeknik Negeri Malang, 2019)
This Community Service Program was an activity to trained all of Lowokwaru 3 Elementary School Committee members in knitting arts. This activity aimed to made the school committee members had some provision of craft art which is expected to earn extra income through independent art craft. The method was implemented by bringing Malang City knitting instructor and knowledge transfer is carried out by discussion and question and answer session through practicum. The results of this community service activity are knitting brooches. It is expected that mothers of SDN Lowokwaru 3 Malang school committee members can apply the art of knitting as a means to earn extra income through independent craft art.